Superselective transcatheter arterial embolization in the treatment of intra-abdominal extralobar pulmonary sequestration - Túlio Fabiano de Oliveira Leite, MD, PhD; Vivalde Faria Lobato Neto, MD (Radiology Case Reports)
Pulmonary sequestration is a congenital anomaly characterized by a mass of nonfunctioning lung parenchyma that receives a systemic arterial blood supply and is mainly located in the thorax. Intra-abdominal pulmonary sequestration, a rare subtype, is typically diagnosed within the first few months of life. We report the case of a term neonate with a history of recurrent left-sided pleural effusion requiring thoracentesis. A CT scan with venous contrast was performed, and an intrabdominal extralobar pulmonary sequestration was identified on the left, associated with a diaphragmatic hernia. The patient underwent embolization of the anomalous branch and reconstruction of the left diaphragm using bovine pericardium.